The Political Economy of the Middle Class in the Dominican Republic : Individualization of Public Goods, Lack of Institutional Trust and Weak Collective Action - Sánchez, Miguel Eduardo (World Bank, Washington, DC, 2012)
This paper tries to uncover some of the hidden factors behind poor public service delivery in the Dominican Republic. By looking at three sector cases, education, health and electricity, it is possible to observe that in this setting of low quality of public services the "middle class" is opting out from the system and adopting private solutions to collective problems. The combination of this opting out behavior with low levels of institutional trust, especially among "middle class" members, fragmented interests and clientelism, among other factors, results in weak collective action and lack of effective demand for improvements in service provision. Some of the tentative policy options to break this sub-optimal equilibrium are i) to build capacity in civil society organizations and help them forming a pro-reform coalition, ii) reduce the gap between the middle class and the poorer by trying to improve the provision of public goods and enlarging the welfare state, and (iii) increase transparency mechanisms and introduce e-government formulas in order to optimize the allocation of public resources.